THE INFLUENCE OF SERVICE, QUALITY, PRICE, AND PLACE ON CUSTOMER LOYALITY (CASE STUDY OF CAFÉ FINARE PALOPO CITY) - Rahmadani, Nurul; Manda Sari; Ari Putra; Nurjannah; Idhasari (Jurnal Manajemen Dan Bisnis, 2023)
The purpose of this study was to determine the effect of service quality, price, and location on customer loyality at Café Finare, Palopo City. This study used a quantitative approach and sampling techniques using incidental sampling method descriptive analysis, validity and reliabillity tests and multiple linear regression analysis ware used as multiple analysis techniques. This study uses multiple analysis techniques. This study uses multiple linear aggression analysis with a significance level of 55% using SPSS.20 data processing techniques. The results of the study partially explain that while the price variable and place variable have no significant effect on customer loyality, while the service quality variable has a significant positive effect on customer loyality, at he same time the service quality, price, and place variables have a significant effect.